CARBON LOSS FROM SEVERAL LANDUSE TYPE ON TROPICAL PEAT LANDS DRAINED - MASWAR, .; HARIDJAJA, O.; SABIHAM, SUPANDI; VAN NOORDWIJK, M. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Conversion Conversion and drainage of peat land stimulate soil organic matter (SOM) mineralization, which substantially increase carbon loss from soils. Carbon losses from peat lands are probably a major component in global greenhouse gas emissions. The objectives of this study are to evaluate carbon loss from several land use of peat drained, and to evaluate factors affected carbon loss from several land use on peat drained. The study was conducted in Nanggroe Aceh Darussalam Province from May 2008 until October 2009. Carbon losses were calculated by interpretation data of bulk density (BD), ash content and carbon content from 0-50 cm top soil of peat lands. Peat lands characteristics i.e. physical, chemical and biological properties were investigated by field observation and analysis of peat soil samples on the laboratorium. The results showed that: 1) ash content and bulk density of the peat are related, indicating the partial lost of soil C during decomposition and compaction, 2) an ?internal tracer? estimate of peat C loss yields estimates of CO2 flux up to 56 t CO2-eq ha-1 year-1 for young oil palm, highly correlated with the measured rates of subsidence of the surface, 3) landscape level variation in maximum water table, salinity and Fe of peat are correlated with measured peat carbon loss.